2020
DOI: 10.3390/ijerph17207627
|View full text |Cite
|
Sign up to set email alerts
|

Changing Income-Related Inequality in Daily Nutrients Intake: A Longitudinal Analysis from China

Abstract: Because of economic reform, dietary pattern in China changed rapidly during the past two decades. Meanwhile, the changes of income and nutrients intake had the same trend. This study aims to measure the income-related inequality in daily nutrients intake and its health-related income mobility over time. Data was sourced from four waves of China Health and Nutrition Survey. Concentration indexes and health-related income mobility indexes were employed to measure the income-related inequality of nutrients intake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
1
3
0
Order By: Relevance
“…Yet, the disaggregation of concentration indexes suggests that income still represents the main barrier to polyphenol and carotenoid intake in 2017–2018. The finding corroborates concerns regarding the role of socioeconomic patterns in determining food consumption patterns and, thus, healthy eating [ 4 , 17 – 22 , 48 ].…”
Section: Discussionsupporting
confidence: 84%
“…Yet, the disaggregation of concentration indexes suggests that income still represents the main barrier to polyphenol and carotenoid intake in 2017–2018. The finding corroborates concerns regarding the role of socioeconomic patterns in determining food consumption patterns and, thus, healthy eating [ 4 , 17 – 22 , 48 ].…”
Section: Discussionsupporting
confidence: 84%
“…The difference may be related to income inequality. Another study showed that high proportions of energy intakes from fats (>30%) were more concentrated among the rich, whereas carbohydrate intakes were larger among the poor [ 30 ]. This is similar to the results of our study, whereby urban residents had higher fat intakes and rural residents had higher carbohydrate intakes.…”
Section: Discussionmentioning
confidence: 99%
“…Low SES may also reflect a woman's lower education level, which could influence her diet and that of her family [49]. Meanwhile, lower education and economic status of women were important factors causing the health disparity between both genders, in which dietary intake was an important mediator [50]. Given these heterogeneous results, it is suggested that more attention should be paid to women with low SES.…”
Section: Discussionmentioning
confidence: 99%